Evolutionary aspects of Parvovirus B-19V associated diseases and their pathogenesis patterns with an emphasis on vaccine development - Das, Piyanki (Virusdisease, 2019)
Parvovirus B-19, a single human pathogenic member of the Parvoviridae family with it’s small ssDNA and non-enveloped structure, is known to cause diseases in erythroid progenitor cells. But a wide range of clinical association of this virus with cells of non-erythroid origins has recently been discovered and many of those are being investigated for such association. Higher substitution rates in due course of evolution has been suggested for this cellular tropism and persistence. In this report, we have summarized the different disease manifestations of B-19 virus and have tried to find out a pattern of pathogenesis. Finally, we have focused on the vaccination strategies available against B-19 virus to correlate these with the mechanisms involved in various diseases caused by this virus.